Assessment and Mapping of Groundwater Quality and its Impact on Soil Properties of Sohna Block in Gurugram District of Haryana State - Bhatia, Rishav; Yadav, Parmod Kumar; Kumar, Satender; Ramprakash; Kumar, Sawan; Dinesh (Journal of Soil Salinity and Water Quality, 2023)
In Sohna block of Gurugram district, a study was conducted to evaluate the quality of the groundwater and determine how it affected the soil qualities. Using a handheld GPS, 79 groundwater samples and 48 soil samples overall were taken from two sites from each category of water, four depths each, in the Sohna block of Gurugram districts. The pH, EC, SAR and RSC ranged from 7.31 - 8.28, 0.75-8.42 (dS m-1), 6.38 – 19.00 (mmol l-1)1/2 and nil to 4.20 (me l-1) in the block. The anions contents in water followed the pattern Cl− > SO42− > HCO3− > NO3− > CO32− whereas the cations were found to be in the following order: Na+> Mg2+ > Ca2+ > K+. The village Isaka had the lowest saturation percentage (28.72%) and the village Abhepur had the highest saturation percentage (35.36%). The settlement of Sohna Rural in the Sohna block has the lowest EC (1.22 dS m-1) of saturated extract. The village of Alipur in Sohna block had the highest EC of saturated extract (8.20 dSm-1) whereas Sanp Ki Nagli (7.66) and Darbaripur (8.47) were the villages in Sohna block with the lowest and highest pH values, respectively. In whole of the block, Cl- and Na+ of the soil saturation extract were significantly and positively correlated with EC, Cl- and EC, Na+ of groundwater used for irrigation, respectively.